Foreign Influence and China’s Export - John, Nwagwu, Chinedu; Samuel Benedict, Edet; Onosuime, Umoru, Georgina (Covenant Journal of Entrepreneurship, 2020)
This paper looks at the idea of foreign influence and how they affect China’s export in the overall. The work chooses to focus on inflow of foreign direct investment (FDI) to China and China’s share of global export (SGE) over the period in view. Making use of existing secondary data, the work adopts the Ex Post Facto research design. Using 21 years’ data from year 1997 to 2017 of FDI & SGE, which were apprised, composed and analyzed for this work. The work used correlation analysis in testing the two hypotheses for this study at a significance level of 0.05 (95%), for the two-tailed test. Findings of this paper reveal that generated p-value for the result (0.000) is less than the level of significant (0.05), implying there is significant positive relationship between FDI & SGE. The Pearson correlation result suggests that there is a high positive relationship between foreign direct investment (FDI) to China and China’s share of global export (SGE) (r = 0.997). This simply implies that there is 99.7% relationship between China Share of Global export (SGE) and foreign direct investment (FDI) to China. This relationship is statistically significant since the generated p-value for the result (0.000) is less than the level of significant (0.05) used for the study. The study recommends amongst others that countries that want to increase their export ratio should not depend solely on their internal or local capacity and capabilities to produce but look to other countries where they can investors to aid their manufacturing sector for onward export.